Es ist nicht die Krake. Die Mafia als Sammelbecken von kriminellen und politischen Organisationen - Violante, Luciano (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The rise of the mafia was very substantially fostered by the specific development policy for the Mezzogiorno. Uncontrolled financial transfers, rapid urbanization processes leading to land and bulding speculation, and weak state structures enabled extensive corruption practices. An effective combat against the mafia can therefore not only rely on police repression, but must also include a political change as well as socialsecurity measures which revoke the mafia’s social hotbed.